Durability and tool wear investigation of HSSE-PM milling cutters within long-term tests. (January 2020) - Monkova, Katarina; Sun, Shufeng; Monka, Peter Pavol; Hloch, Sergej; Belan, Miroslav
Highlights: The research of a tool wear and tool durability is an important issue of manufacturing today. A synergic effect of cutting speed and depth on the wear of HSS-PM cutters was investigated. Several types of wears were identified on the cutting tools resulted in a worse quality of the machined surface. Tool wear development has an impact on the machining process stability and it affects also a change of chip. Abstract: Tool durability is an important parameter in the evaluation of the performance of the cutting tools and inserts. It is directly connected with tool wear that significantly affects the quality of the workpiece. Only from an understanding of the nature behind the machining process in given conditions (a combination of cutting parameters, machined material, tool characteristics including its material, etc.), a tool wear mechanism can be identified and consequently estimate the tool life and its durability. The article deals with a durability of the milling cutters produced from the high-speed steel via powder metallurgy (HSS-PM) and coated by AlTiN coat. Effects of a varying combination of cutting speed and depth of cut to tool wear and surface roughness had been also investigated within the long-term tests. Conventional milling was selected as a technology to test the durability of HSSE-PM shank milling cutters at which the steel 1.4301 (AISI 304, DIN 1.4301) as a material that is very difficult to cut was machined without a coolant. Within the research, the tool wears in several points on a cutting edge were evaluated, while several types of tool wear have been identified. Achieved data were statistically processed and based on them the development of the tool wear of individual milling cutters in time has been processed as well as a dependency of the tool wear on cutting speed and cutting depth has been plotted. The accompanying phenomenon of tool wear increasing is a deteriorated quality of surface roughness and change in a chip formation. The average values of surface roughness Ra relative to machining time achieved by milling cutters working at a specific depth of cut were also assessed. The pictures of the chips approved that along with tool wear increasing the chip becomes thinner with larger rugged relief.